2014
DOI: 10.1177/1066896914563391
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Nephroma/Mixed Epithelial Stromal Tumor

Abstract: Cystic nephroma (CN) is a rare, benign, renal neoplasm composed of epithelial and stromal elements. Only about 200 cases have been reported since 1892 and recurrence has rarely been observed. We report a 32-year-old Hispanic woman, with a history of a right, complex cystic, renal mass treated by robotic decortication 2 years ago, who presented with flank pain, hematuria, and recurrent urinary tract infection. A magnetic resonance imaging study showed a 3.4-cm multicystic lesion with thickened septa and enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…It is similar to cystic malign pathologies in radiological terms and is reported as case presentations in literature. 23 Oncocytoma was found in 7 (3.4%) patients in our study and it was detected as the most common benign mass following AML concordantly with the literature. Although xanthogranulomatous pyelonephritis which occurs quite rarely due to chronic infection and the resultant renal mass images are benign lesions, they may not always present specific radiological and clinical findings.…”
Section: Discussionsupporting
confidence: 91%
“…It is similar to cystic malign pathologies in radiological terms and is reported as case presentations in literature. 23 Oncocytoma was found in 7 (3.4%) patients in our study and it was detected as the most common benign mass following AML concordantly with the literature. Although xanthogranulomatous pyelonephritis which occurs quite rarely due to chronic infection and the resultant renal mass images are benign lesions, they may not always present specific radiological and clinical findings.…”
Section: Discussionsupporting
confidence: 91%
“…However, the clinical significance of such tumor extension is at present unknown and a longer follow-up may be needed to determine the biology of such tumors. Caution is advised since MEST tumors have been reported to recur locally after incomplete excision [ 38 ] and peritoneal seeding following incomplete resection, resulting in a separate paracolonic MEST, has also been reported [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…[15] Immunohistochemical studies have revealed that stromal contents stain mostly with CD10, calretinin, inhibin, estrogen, and progesteron receptors, while epithelial component has an increased affinity to cytokeratin. [10] The most recent evidence demonstrate that in adult population, tumors with initial diagnosis of CN essentially represent mixed epithelial, and stromal tumors from genetic, and histological perspectives. [17] However some authors think that CN, mixed epithelial, and stromal tumors are different spectrums of the same entity.…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence or metastasis is limited to a few cases, and it has been reported that local recurrence especially in patients who underwent partial nephrectomy is a possibility which might be related with incomplete resection. [3,10] Contrarily, Castillo et al [4] presented a series of 29 cases, and couldn't encounter any postoperative local recurrence or metastasis. Also in our case we didn't observe any local recurrence or metastasis.…”
Section: Discussionmentioning
confidence: 99%